2020
DOI: 10.1038/s41467-020-15876-8
|View full text |Cite
|
Sign up to set email alerts
|

Aspartate aminotransferase Rv3722c governs aspartate-dependent nitrogen metabolism in Mycobacterium tuberculosis

Abstract: Gene rv3722c of Mycobacterium tuberculosis is essential for in vitro growth, and encodes a putative pyridoxal phosphate-binding protein of unknown function. Here we use metabolomic, genetic and structural approaches to show that Rv3722c is the primary aspartate aminotransferase of M. tuberculosis, and mediates an essential but underrecognized role in metabolism: nitrogen distribution. Rv3722c deficiency leads to virulence attenuation in macrophages and mice. Our results identify aspartate biosynthesis and nitr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 72 publications
1
49
0
1
Order By: Relevance
“…It has been shown that aspartate aminotransferase R3722c mediates an essential role in metabolism and is required for virulence of M.tb ( Jansen et al., 2020 ). Previously, we constructed a filtered PPI network with 441 PPIs between M.tb membrane and secreted proteins and host immunity-related proteins ( Yang et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that aspartate aminotransferase R3722c mediates an essential role in metabolism and is required for virulence of M.tb ( Jansen et al., 2020 ). Previously, we constructed a filtered PPI network with 441 PPIs between M.tb membrane and secreted proteins and host immunity-related proteins ( Yang et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…As Rv3722c is essential for M.tb growth in vitro and interacts with host proteins such as TRAF3 (Yang et al, 2018;Jansen et al, 2020), we hypothesized this protein might play an important role Verification of the protein-protein interaction by Y2H assay. Rv3722c in the pmBD destination vector was used as bait.…”
Section: Rv3722c Promotes Mtb Survival In Murine Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…ABPP can help address this challenge, as ABP-labeling directly signifies protein function (Adam et al, 2004 ; Kamat et al, 2015 ; Xu et al, 2015 ; Martell et al, 2016 ; Ortega et al, 2018 ; Elahi et al, 2019 ). This is especially true when accompanying metabolomics data can provide added confidence (Jansen et al, 2020 ). ABPP can also identify viable whole cells in complex samples based on a certain function without needing any information beforehand, which may aid in the study of un-culturable microbes with poorly characterized genomes.…”
Section: Functional Characterization Of the Gut Microbiome Using Actimentioning
confidence: 99%